(3ecGQe GdCNdGbs - (3eMeO Hf LYaQ Hf eMeO Hf Sgd CHh HcQ GdNQGFWj GdSGeQj , CHh HcQ,J (B327 (3g` s
(3ChdgG (B:s
(3jHOC HGH GdMK Ydi GdCNdGb GdUGdMI s
(3BNQgG (B:s
(3jfJgi HHGH GdQbG hGdYhP s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B154s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs